Pengaruh Dukungan Organisasi dan Psychological Safety Terhadap Perilaku Inovatif Karyawan dalam Lingkungan Kerja Digital di PT Bank Kalteng Kota Palangka Raya - Anike Retawati; Muhamad Ruzaini Abdi; Roni Kurnia Sukmaputra (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the influence of organizational support and psychological safety on employees' innovative behavior in a digital work environment. The study uses a quantitative approach with an explanatory research type. Data was collected through questionnaires distributed to employees of PT Bank Kalteng in Palangka Raya who use digital systems in their daily work activities. The sampling technique used is purposive sampling. Data analysis was done using multiple linear regression with the help of SPSS software, which includes validity and reliability tests, classical assumption tests, t-tests, F-tests, and the coefficient of determination. Research results show that organizational support has a positive and significant effect on employees' innovative behavior. Psychological safety also has a positive and significant impact on employees' innovative behavior. Together, organizational support and psychological safety significantly influence employees' innovative behavior in a digital work environment. These findings suggest that employees' innovative behavior is not only determined by the use of technology, but also by how much the organization provides support, facilities, rewards, and creates a sense of psychological safety for employees to share ideas, try new ways of working, and participate in work innovation. This study implies that digital transformation in the banking sector needs to be accompanied by strengthening organizational support and an open work culture so that employees can adapt and innovate continuously.